Power through Translanguaging in Writing Class Discourse: An Indonesian Case Study - Angga Maulana; Wawan Gunawan; Mahardhika Zifana (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
This study looks at how power is established when translanguaging occurs in writing class discourse using English as the language of instruction. It is a qualitative research method using a case study methodology. Data collection methods included semi-structured interviews with class lecturers, focus groups with nine students, and classroom observations. Fairclough's (2001) notions of "power behind discourse" and "power in discourse" serve as the analytical foundation for this study. He defined three types of aspects: subjects, or the "subject positions" that persons might hold; connections, or the social ties that people develop during talks; and content, or what is said or done. The findings demonstrated that translanguaging helps students conceive complicated concepts, negotiate meaning, and preserve their language and cultural identities. It also promotes collaborative learning environments, which normalize language variety while increasing students' confidence and academic autonomy. Translanguaging helps students to use their language resources, which promotes agency and critical engagement with academic information. However, it also emphasizes the power dynamics in students' linguistic identities, in which the usage of many languages threatens English's supremacy. By analyzing these interactions, this study emphasizes the need of inclusive instructional practices that empower students while respecting their language variety.